Hedging effectiveness of crude palm oil futures market in Malaysia - Ong, Tze San; Tan, Wei Fong; Teh, Boon Heng (IDOSI Publications, 2012)
This paper investigated the hedging effectiveness of crude palm oil futures market in Malaysia from January 2009 to June 2011 which traded under Bursa Malaysia Derivatives Berhad. Ordinary Least Squared (OLS) method was used to compute Minimum-Variance hedging ratio (MVHR), R-squared and hedging effectiveness by using daily data from settlement price of crude palm oil futures contracts and spot price of crude palm oil. The empirical results indicate that the highest hedging ratio has been observed in the February 2009 FCPO contract, 66.7660%. Meanwhile, the lowest hedging ratio occurs in June 2010 contract which is 35.7131%. In overall, Malaysia FCPO market only provides a low level of hedging effectiveness (19% - 53%) due to less volatility of CPO spot price. As a conclusion, hedging effectiveness of crude palm oil futures market in Malaysia shows a low level of hedging effectiveness. This result indicates that the spot price of crude palm oil in Malaysia is relatively stable and consistent over the period of 2009 to 2011. The outcome of this research intends to provide hedging information of the Malaysia FCPO futures market in order to cover risk exposure by holding FCPO in BMD.